Non-Thermal Processing of a Protein Functional Beverage Using Pulsed Electric Fields: Escherichia coli Inactivation and Effect on Proteins - Alzahrani, Mona (2022)
The application of pulsed electric fields (PEFs) for the inactivation of Escherichia coli, suspended in a protein shake beverage and diluted with sterilized distilled water was carried out. Square bipolar pulses in the range of 25–40 kV/cm electric field intensities were applied at different frequencies (400–900 Hz) to investigate the effect of different PEF conditions on the microbial population and proteins relevant to this functional beverage. The treatment temperature was kept below the lethal temperature of the microorganism under investigation. As power consumption plays an important role in the efficiency of the PEF application, the dissipated power was also estimated. Four log reductions in the E. coli population were obtained with 10 pulses at a 40 kV/cm field intensity and 25 pulses at a 25 kV/cm field intensity. PEF-treated whey-protein concentrates showed less denaturation in proteins than thermally treated concentrates, especially for lower electric field intensities (0% denaturation ± 0.007 at 25 kV/cm and 900 Hz, 4.41% denaturation ± 0.008 at 40 kV/cm and 400 Hz). Soy protein isolates manifested high sensitivity to PEF processing and resulted in denaturation and aggregation in the protein structure.